2021
DOI: 10.1186/s40168-021-01099-6
|View full text |Cite
|
Sign up to set email alerts
|

Arms race in a cell: genomic, transcriptomic, and proteomic insights into intracellular phage–bacteria interplay in deep-sea snail holobionts

Abstract: Background Deep-sea animals in hydrothermal vents often form endosymbioses with chemosynthetic bacteria. Endosymbionts serve essential biochemical and ecological functions, but the prokaryotic viruses (phages) that determine their fate are unknown. Results We conducted metagenomic analysis of a deep-sea vent snail. We assembled four genome bins for Caudovirales phages that had developed dual endosymbiosis with sulphur-oxidising bacteria (SOB) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“… 63 , 64 Even more rarely reported are active phages infecting bacterial endosymbionts in the deep ocean. 65 , 66 Our identification of proHMS1 within the S . annulatum endosymbiont undergoing a lytic cycle offers an opportunity to understand the tripartite interactions among the phage, the endosymbiont and the animal host.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“… 63 , 64 Even more rarely reported are active phages infecting bacterial endosymbionts in the deep ocean. 65 , 66 Our identification of proHMS1 within the S . annulatum endosymbiont undergoing a lytic cycle offers an opportunity to understand the tripartite interactions among the phage, the endosymbiont and the animal host.…”
Section: Discussionmentioning
confidence: 82%
“… 19 In addition, the highly expressed DNA methyltransferase HhaI gene of proHMS1 likely plays a counter-defense role in resisting defense systems of the symbiont like that happened in the deep-sea snail holobiont. 66 Our work thus provides a new case of internal phage-bacterial interactions in deep-sea chemosymbiosis ecosystems.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, a few studies have shown that viruses inhabit various organs. For example, the esophageal glands of the deep-sea snail Gigantopelta aegis harbor four populations of tailed phages (Zhou et al 2021b), and the intestines and hepatopancreases of the mussels Mytilus edulis and Modiolus modiolus and the oyster Ostrea edulis contain enteric viruses (Myrmel et al 2004). Tissuespecific signatures can be found by sampling viruses from different tissues and organs and performing sequencing for further analysis.…”
Section: Intra-and Interspecies Patternsmentioning
confidence: 99%
“…Depending on their infection strategies and genetic traits, phages may actively participate in the establishment, maintenance, and breakdown of the symbiotic systems of marine invertebrates. Among marine invertebrates, viromes in sponges and corals are highly diverse and relatively well studied, generating a large volume of genomic information that expands our knowledge of phage diversity, phage-host interactions, and phage life strategies (Engelberts et al 2022, Zhou et al 2021b. Given the high diversity of marine invertebrate animals, novel ecological interactions between phages and bacteria and their influences on marine invertebrate hosts will be revealed, particularly for underexplored marine invertebrates from extreme marine habitats, such as hydrothermal vents and cold seeps (Bass et al 2021, Holt et al 2022.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%
“…We previously developed Autometa, an automated binning pipeline that is able to effectively recover genomes from highly convoluted environmental and non-model host-associated microbial communities (3). This tool has seen widespread use in environments ranging from marine, freshwater and terrestrial samples, including corals (4), red algae (5), kinetoplastids (6), deep sea geothermal vents (7)(8)(9), sponges (10)(11)(12), coastal sediments (13), stromatolites (14), seaweeds (15), shipworms (16), plateau lakes (17,18), hot springs (19,20), contaminated rivers (21), beetles (22)(23)(24)(25), Kickxellomycotina fungi (26), Ensifera insects (27), fermented agave (28,29), a marsh orchid rhizobiome (30), domesticated cattle (31,32), mice (33) and human gut (34), periodontal (35) as well as urinary tract (36) microbiomes. As a consequence of Autometa's widespread use, both non-technical and technical researchers alike have communicated their frustrations regarding the ease of installation as well as the efficiency and robustness throughout the various stages of the Autometa workflow.…”
Section: Introductionmentioning
confidence: 99%